Characterization of hardening behaviors of 4130 Steel, OFHC Copper, Ti6Al4V alloy considering ultra-high strain rates and high temperatures. (October 2017) - Piao, MingJun; Huh, Hoon; Lee, Ikjin; Park, Leeju
Highlights: Hardening behaviors at ultra-high strain rates have been characterized. A hybrid optimization approach is used to characterize hardening behaviors. Thermal softening effect is investigated at different strain rates. Sequentially deformed shapes have been considered from the Taylor impact tests. Abstract: This paper is concerned with the characterization of dynamic hardening behaviors of metallic materials at ultra-high strain rates ranging from 10 4  s −1 to 10 6  s −1 . As typical metallic materials, three kinds of materials are selected for body centered cubic (BCC), face centered cubic (FCC), and hexagonal close packed (HCP) structures: 4130 steel; OFHC copper; and Ti6Al4V alloy, respectively. In order to investigate the hardening behaviors for the three materials, uniaxial tensile tests are conducted at room temperature of 25 °C and a wide range of strain rates from 10 −3  s −1 to 10 3  s −1 with the Instron 5583, a high speed material testing machine (HSMTM), and a tension split Hopkinson pressure bar (TSHB). To consider the thermal softening effect at different strain rates, tensile tests are additionally performed at an elevated temperature up to 200 °C and strain rates of 10 −3  s −1, 10 −1  s −1, and 10 2  s −1 . Hardening curves obtained from several experiments are expressed with a constitutive model by multiplying a strain hardening term, a strain rate hardening term, and a thermal softening term to describe material behaviors at large plastic strain, high strain rate, and elevated temperature, respectively. A well fitted constitutive model is utilized to interpolate and extrapolate stress–strain relation from low to ultra-high strain rates. The experimental and extrapolated data are implemented into finite element simulations as the preliminary material properties before calibration. A hybrid experimental-numerical approach is applied to precisely calibrate the extrapolated hardening behaviors at ultra-high strain rates by utilizing the Taylor impact test results. During the Taylor impact tests, images of several sequentially deformed shapes of projectiles are acquired by a high speed camera to compare with numerical simulation results. The stress–strain curves after calibration give notable improvements in the accuracy of numerical estimation of the deforming shapes of projectiles at ultra-high strain rates. Graphical abstract: